Bridging research integrity and global health epidemiology (BRIDGE) guidelines: explanation and elaboration. Issue 10 (28th October 2020) - Alba, Sandra; Lenglet, Annick; Verdonck, Kristien; Roth, Johanna; Patil, Rutuja; Mendoza, Walter; Juvekar, Sanjay; Rumisha, Susan F
Abstract : Over the past decade, two movements have profoundly changed the environment in which global health epidemiologists work: research integrity and research fairness. Both ought to be equally nurtured by global health epidemiologists who aim to produce high quality impactful research. Yet bridging between these two aspirations can lead to practical and ethical dilemmas. In the light of these reflections we have proposed the BRIDGE guidelines for the conduct of fair global health epidemiology, targeted at stakeholders involved in the commissioning, conduct, appraisal and publication of global health research. The guidelines follow the conduct of a study chronologically from the early stages of study preparation until the dissemination and communication of findings. They can be used as a checklist by research teams, funders and other stakeholders to ensure that a study is conducted in line with both research integrity and research fairness principles. In this paper we offer a detailed explanation for each item of the BRIDGE guidelines. We have focused on practical implementation issues, making this document most of interest to those who are actually conducting the epidemiological work.